Inverse coefficient problems for a transport equation by local Carleman estimate. (23rd September 2019) - Cannarsa, P; Floridia, G; Gölgeleyen, F; Yamamoto, M
Abstract: We consider the transport equation in where is a bounded domain, and discuss two inverse problems which consist of determining a vector-valued function or a real-valued function by initial values and data on a subboundary of . Our results are conditional stability of Hölder type in a subdomain D provided that the outward normal component of is positive on . The proofs are based on a Carleman estimate where the weight function depends on H .